The Influence of Digital Infrastructure Readiness and Regulatory Effectiveness on Islamic Financial Inclusion through FinTech: An Analysis Using Structural Equation Modeling (SEM-PLS) - Dede Nurdiansyah (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study examines the influence of digital infrastructure readiness and regulatory effectiveness on Islamic financial inclusion through the role of FinTech using the Partial Least Squares-based Structural Equation Modeling method (SEM-PLS). The analysis results show that both factors have a positive and significant influence on Islamic financial inclusion, with FinTech acting as the main mediator. Regulatory effectiveness is proven to increase public trust in FinTech while ensuring compliance with Sharia principles, while digital infrastructure readiness expands FinTech access through support of stable internet networks and integrated payment systems. FinTech itself plays an important role in expanding access to Sharia finance, especially for communities previously unreachable by the conventional financial system. However, the direct influence of digital infrastructure readiness on Islamic financial inclusion is relatively smaller, indicating that digital infrastructure does not directly provide a major impact without the role of FinTech as a connector. These findings provide practical implications for policymakers, regulators, and FinTech service providers in designing policies that support the development of inclusive and Sharia-compliant FinTech. This study contributes to the Islamic finance literature by emphasizing the importance of integrating technology, regulation, and Sharia principles to achieve broader and more sustainable financial inclusion in the digital era.